INVESTIGATING OF FINANCIAL DISTRESS IN HEALTHCARE INDUSTRIES: THE MODERATING ROLE OF PROFITABILITY - Andaris, Ibnu; Dasman, Sunita (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to investigate the factors of liquidity, leverage, and company size, with profitability serving as a moderating component in relation to financial distress. The focus of the research is directed at health sector issuers listed on the Indonesia Stock Exchange during the period 2020-2024, considering that this sector is very vulnerable to financial pressures due to fluctuations in operational costs and market dynamics. The theoretical analysis employs agency theory and signaling theory as its primary frameworks. This study uses quantitative methodologies. This study utilizes secondary data obtained from the official website of the Indonesia Stock Exchange. This research used a sample of 17 firms. This study utilizes panel data moderation regression analysis, facilitated by Eviews 12 software. The study findings indicate that, to some extent, the liquidity variable and firm size do not significantly influence financial distress. partially, the leverage factors significantly influence financial distress. It was shown that profitability moderates the association between liquidity and firm size concerning financial distress, however the leverage variable's relationship with financial distress is not moderated by profitability. This study underscores the need for healthcare organizations to exercise more prudence in managing liquidity and leverage to prevent financial disaster.